Staying the Decline in Union Membership : Union Organizing in Ontario, 1985-1999 - Yates, Charlotte (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2000)
In response to a sense of crisis precipitated by the 1995 election of the provincial Conservative govemment in Ontario and more anti-union employers, unions in Ontario have increased resources invested in and priority attached to organizing the unorganized. This article examines how unions have reoriented their organizing strategies to increase organizing effort in the private service sector and amongst women while at the same time experimenting with certain innovative rank-and-file intensive strategies that have significant positive effects on the outcome of organizing drives, The paper concludes that if unions follow through with this renewed commitment to organizing, they are likely to prevent a more serious membership crisis from erupting.